Enhancing Maritime Term-Based Communication Through Communicative Activities Amongs Students In Yogyakarta Maritime Academy - Sri Sartini (Sekolah Tinggi Maritim Yogyakarta, 2018)
This research is aimed at getting to know the problem of cadets in Nautical Science Study Program academic year 2016/2017 in their second semester grade upon their way to master communication skill especially in the practice of using Maritime term-based communication. Knowing the problem, researcher scaffold the cadets as many as 30 cadets with the typically teaching and learning process which is much concerned to the learners. This research was conducted in an action research where it included some cycles that is teaching and learning cycles, diagnostic cycle, treatment or scaffolding and taking a conclusion. The result of the study shows that communicative approach taught by Maritime English lecturer which emphasizes cadets to speak is not that simple to be practically given to them. It is due to the different native speaking country or cultural background that does not customize them to speak up. Scaffolding them by implementing the use of Standard Marine Communication Phrases in class combined with the type of teaching approach which higlight to student-centered learning is proven giving better achievement of teaching and learning process.Thirteen out of the twenty three cadets or it is more than a half percentage of the class achieved better skill in communication in English especially in maritime context by the use of Standard Marine Communication Phrases.